Nucleophilic Addition Reactions of Nitriles to Nitrones under Mild Silylation Conditions - Yoshimura, Fumihiko; Abe, Taiki; Tanino, Keiji (Synlett, 2014)
In the presence of triethylsilyl trifluoromethanesulfonate and triethylamine, aliphatic nitriles undergo addition reactions with aldonitrones under non-basic, mild conditions, providing O-triethylsilyl ethers of β-N-hydroxyamino nitriles with high yield. The reaction appears to proceed through formation of an N-silyl ketene imine in situ followed by a Mannich-type reaction.
Keywords: nucleophilic addition; nitriles; nitrones; amines; hydroxylamine